Anxiously attached eaudiobook Becoming more secure in life and love. - Baum, Jessica (Penguin Audio, 2022)
A road map for building strong and secure relationships for those who struggle with anxiety in their romantic connections. An estimated 47 million Americans identify as having an anxious attachment style, which can make being in relationships turbulent and emotionally taxing for them. According to groundbreaking research in the field of attachment, anxious types are more prone to insecurity, jealousy, codependency, and other behaviors that get in the way of finding and sustaining love. In Anxiously Attached , seasoned psychotherapist and couples counselor Jessica Baum guides readers through understanding their attachment style at its core and building the inner strength and self-love that will lead them to more secure and satisfying relationships.   Developed over ten years in private practice, Baum’s signature Self-full® Method has helped her clients get off the toxic roller coaster of anxious attachment and discover the secure and mutually supportive relationships they deserve. In this book readers will learn how to:   Create boundaries to safeguard their sense of self-sovereignty in relationships Communicate to their partners what they need to feel safe and secure in the relationship Develop a secure sense of self-worth and emotional stability Learn the true meaning of a healthy/interdependent relationship and how to establish one with their partner or future partner. Discover a compassionate path towards healing through experiences like mediation practices where they can start to develop more insight into their internal landscape. Attain a deep understanding of the anxious-avoidant dance that is extremely common in intimacy struggles.   Anxiously Attached offers a practical and holistic approach for overcoming anxious attachment issues to discover happier, more fulfilling relationships.